2021
DOI: 10.1371/journal.pone.0245353
|View full text |Cite
|
Sign up to set email alerts
|

Detection of postural control in early Parkinson’s disease: Clinical testing vs. modulation of center of pressure

Abstract: Introduction Little is known about the early stage balance changes in PD. Many clinicians assume that there are no postural issues in early PD because of failure to identify them on bedside and clinical testing. Here, we quantify balance changes in early and moderate stage PD and compared these values to healthy controls (HC) using clinical assessments of balance and posturography. Methods We compared 15 HC with 15 early PD (PD-II; Hoehn and Yahr stage II) and 15 moderate PD (PD-III; H&Y stage III). Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 40 publications
0
38
1
2
Order By: Relevance
“…Several investigations have proposed postural sway measures that could become markers of age effect on postural control or of increased fall risk in healthy ageing and in disease conditions [e.g., (14)(15)(16)(17)(18)(19)]. On a different vein, it has been suggested that sway may not be a reliable marker of functional balance performance (20), and it seems that traditional measures of postural sway are not always able to differentiate between healthy subjects and patients with movement disorders (21,22). These uncertainties are partly dependent on technical or practical reasons, such as the recording apparatus, the duration of the acquisition period (23,24), the frequency of sampling of the CoP excursions, the filtering procedures, and other confounding subject-related circumstances such as fatigue (25), not to speak of the instruction given to the participants and the ample interindividual variability (17,(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have proposed postural sway measures that could become markers of age effect on postural control or of increased fall risk in healthy ageing and in disease conditions [e.g., (14)(15)(16)(17)(18)(19)]. On a different vein, it has been suggested that sway may not be a reliable marker of functional balance performance (20), and it seems that traditional measures of postural sway are not always able to differentiate between healthy subjects and patients with movement disorders (21,22). These uncertainties are partly dependent on technical or practical reasons, such as the recording apparatus, the duration of the acquisition period (23,24), the frequency of sampling of the CoP excursions, the filtering procedures, and other confounding subject-related circumstances such as fatigue (25), not to speak of the instruction given to the participants and the ample interindividual variability (17,(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…When the sway amplitude in the ML direction exceeds a threshold range, the intermittent control mechanism will be triggered ( 39 ). It has been reported that COP oscillations below 0.5 Hz were exacerbated in an early and moderate PD relative to the healthy group in the state of EO ( 40 ). Since all the participants were in an early or moderate stage of the disease, balance impairments in the ML direction were not obvious and could not be discriminated against during static standing.…”
Section: Discussionmentioning
confidence: 99%
“… Sample entropy (SE): the sample entropy is a measure for assessing the regularity of a signal by calculating the probability that windows with length m remain similar within a tolerance r at the next data point [ 18 , 19 ]. We used input parameters m = 3 and r = − 0.2 as previously done [ 20 ]. …”
Section: Methodsmentioning
confidence: 99%